2017
DOI: 10.1159/000458538
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of a Treat-and-Extend Regimen of Aflibercept for Exudative Age-Related Macular Degeneration

Abstract: Purpose: The aim of this study was to investigate the 1-year outcomes of treat-and-extend aflibercept for exudative age-related macular degeneration (AMD) in Japan. Procedures: Clinical records of 67 patients (67 eyes) were reviewed. Monthly aflibercept was administered until resolution of exudation and maximal reduction of pigment epithelial detachment. Injection intervals were extended by 2-week units up to 12 weeks if no exudation was observed and shortened for recurrence. Results: Mean best-corrected visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Our study demonstrated that an IVT-AFL T&E regimen, following initial monthly dosing, can be effective in the first year of treatment and continuously efficacious in the second year using either a 2-or 4-week adjustment based on defined criteria for interval extension, maintenance, or shortening. In other studies, injection intervals were adjusted by 2-week increments with a set minimum injection interval of 4 weeks and a maximum of 12 weeks [21][22][23]. In ALTAIR, 57-60% of patients achieved a last injection interval of at least 12 weeks up to week 96, compared with 17-37% of patients in other prospective studies of ranibizumab and IVT-AFL T&E regimens [21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that an IVT-AFL T&E regimen, following initial monthly dosing, can be effective in the first year of treatment and continuously efficacious in the second year using either a 2-or 4-week adjustment based on defined criteria for interval extension, maintenance, or shortening. In other studies, injection intervals were adjusted by 2-week increments with a set minimum injection interval of 4 weeks and a maximum of 12 weeks [21][22][23]. In ALTAIR, 57-60% of patients achieved a last injection interval of at least 12 weeks up to week 96, compared with 17-37% of patients in other prospective studies of ranibizumab and IVT-AFL T&E regimens [21,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 23 , 24 In the VIEW studies, monthly and bimonthly aflibercept treatment after 3 loading doses resulted in 8-9 letters of visual increase at month 12. 8 Yamamoto et al 25 evaluated the efficacy of treat-and-extend regimen with aflibercept in nAMD and demonstrated 1.5 lines of visual increase at month 12. In all of these and other randomized controlled studies, the mean injection number during the first year was reported as at least 8.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these and other randomized controlled studies, the mean injection number during the first year was reported as at least 8. 6 , 8 , 12 , 23 , 24 , 25 On the other hand, reaching this injection number seems nearly impossible with the PRN treatment regimen in real life. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Most of the retrospective real-life studies reported the injection number as 3-4 during the first year.…”
Section: Discussionmentioning
confidence: 99%
“…In real-world practice, the majority of patients with AMD are given pro re nata or treat-and-extend (TAE) regimens to reduce various physical and financial burdens on both the patients and physicians,1922 and a TAE dosing regimen showed similar visual outcomes with less injection numbers compared to fixed-dosing regimens 23…”
Section: Introductionmentioning
confidence: 99%